A Review of Theory of Mind in Aging in Clinical Situations - Ayten EKİNCİ (Yaşlı Sorunları Araştırma Derneği, 2023)
Mechanisms that enable older adults to lead active social lives have been regarded as promising ways to promote health and well-being into old age. Theory of Mind (ToM) is one of the most important social cognitive abilities to maintain efficient and compatible social functioning. While lighting the changes in ToM in healthy aging, it is emphasized that research should also evaluate the changes that occur with pathological aging. Understanding the studies that analyze ToM functionality is crucial as these impairments worsen patients' quality of life and pose a risk that may increase patients' social isolation. Impaired ToM which represents a fundamental feature of most clinical conditions in older patients, has been described in various neurological and psychiatric disorders. In addition, extensive research has been conducted on patients with dementia and schizophrenia. There are mechanisms that mediate the role of effective processes in the ability to make sense of the behavior of others and to plan socially appropriate actions. In this review, based on different mechanisms deepening research on ToM related to neurodegenerative and psychiatric diseases in older adults has been evaluated. As the current situation on the subject is still obscure, this review may offer the opportunity to explore limitations and be a starting point for future research. In addition, aim to increase awareness by drawing attention to the crucial role of including ToM function scales in neuropsychological protocols for detecting pathological cases or evaluating early-stage symptoms and following their progression.